Molecular cloning, expression and characterization of a bacteriophage JN01 endolysin and its antibacterial activity against E. coli O157:H7. (1st August 2022) - Shen, Kai-Sheng; Shu, Mei; Tang, Meng-Xuan; Yang, Wen-Yu; Wang, Shu-Chao; Zhong, Chan; Wu, Guo-Ping
Abstract: Endolysins encoded by bacteriophages are considered bacteriostatic agents for the prevention of pathogenic bacteria proliferations. In this study, a possible endolysin from bacteriophage JN01, namely LysJN01, belonging to the lysozyme-like superfamily, was cloned, expressed and characterized. Meanwhile, the bactericidal activity of recombinant LysJN01 (rLysJN01) against E. coli O157:H7 was evaluated in Tris-HCl buffer and on lettuce. Recombinant LysJN01(rLysJN01) consists of a single domain with a molecular weight of about 20 kDa. The yield of rLysJN01 was about 20 mg/L rLysJN01 had a strong lytic activity against chloroform treated E. coli O157:H7. It combined with EDTA could also significantly lyse E. coli O157:H7. Afterward, rlysJN01 showed high enzymatic activity stability at temperature (4–95 O C) and pH (5.0–11.0). Moreover, it also revealed a broad spectrum of antimicrobial activity against Gram-negative pathogens, such as E. coli, Salmonella and Pseudomonas aeruginosa . Furthermore, the counts of E. coli O157:H7 on contaminated lettuce was significantly reduced by 91.6% and 97.8% after treatment with a combination of 60 μg/mL rLysJN01 and 0.5 mmol/L EDTA for 30 min and 60 min, respectively. All these results indicated that rLysJN01 is a potential and efficient bacteriostatic agent for biocontrol of E. coli O157:H7. Highlights: The endolysin LysJN01 of phage JN01 was soluble recombinant expressed and characterized. RLysJN01 had stable lytic activity against chloroform treated E. coli O157:H7. RlysJN01 had a broad spectrum of antibacterial activity against Gram-negative bacteria. RLysJN01 combined with EDTA reduced E. coli O157:H7 on lettuce by 97.8% in 1 h.